Perbandingan Efektifitas Latihan Rom Aktif Dan Akupresur Terhadap Kekuatan Otot Ekstremitas Atas Pada Pasien Stroke Non Hemoragik Di Ruang Rawat Inap Rsud Dr. Haryoto Lumajang - Widya Addiarto; Zainal Abidin; Yeni Puspitasari; Mariani (PROFESSIONAL HEALTH JOURNAL, 2023)
Stroke is a clinical syndrome that begins suddenly, progressively, in the form of focal or global neurological deficits that lasts 24 hours or more and can cause death. This is caused by nontraumatic cerebral blood flow disorders. The purpose of this study was to compare the effectiveness of active ROM and acupressure exercises on upper limb muscle strength in non-hemorrhagic stroke patients in the inpatient room of RSUD Dr. Haryoto Lumajang. The research method used was a pre-experimental design with the type of pre-test and post-test one group design. With a sample of 36 respondents with the Accidental Sampling technique and the test used was the Wilcoxon test. From the results before being given the ROM treatment, 11 respondents (61.1%) had poor muscle tone and before being given the acupressure treatment, 15 respondents (83.3%) had poor muscle tone. From the results after being given ROM treatment, 13 respondents (72.2%) had moderately good muscle tone and after being given the acupressure treatment, 14 respondents (77.8%) had poor muscle tone. The results of the Mann-Whitney analysis test obtained α = 0.003, which means that there is a comparison of the effectiveness of active ROM exercises and acupressure on upper limb muscle strength in non-hemorrhagic stroke patients. It is expected that patients with stroke will always try to practice ROM independently which has been taught by health workers, for the patient's family to participate and motivate patients to do ROM exercises to accelerate the healing of stroke patients. Keywords: Active ROM Exercises, Acupressure, Upper Extremity Muscle Strength, Non Hemorrhagic Stroke